Pengaruh Kesadaran Diri (Self-Awareness) terhadap Pengalaman Nilai-Nilai Akhlak Siswa MA Raudhatut Tholibin Kembaran - Mita Alisah Tazkiyah; Ellen Prima (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2026)
This study aims to understand the impact of Self (Self-Awareness) on the Practice of Moral Values ​​among students at MA Raudhatut Tholibin Kembaran. This study used a quantitative approach with a linear regression analysis design. The study population consisted of 10th and 11th grade students, with approximately 15 students selected as respondents. Data collection was conducted through questionnaires. The research instrument was evaluated using validity and reliability tests, while data analysis was conducted using normality, linearity, linear regression, hypothesis testing (t-test), and the coefficient of determination (R2). The results showed that each instrument item was considered valid with a calculated r value greater than the table r (0.514) and reliable with a Cronbach's Alpha value of 0.846 for the Self variable and 0.821 for the Practice of Moral Values ​​variable. The results of the hypothesis test showed a significance level of approximately 0.001 (<0.05), indicating a positive and significant relationship between Self-Awareness and the Practice of Moral Values. The coefficient of determination (R2) of 0.621 indicates that self-awareness contributes 62.1% to the practice of moral values, while other factors outside the study contribute 37.9%. Students' practice of moral values ​​can be encouraged by increasing self-awareness.